The Palamite Ideas for the Divine Light of the Image in the 14th Century Churches of Thessaloniki - Stefanova, Lyuboira (Forum Theologicum Sardicense, 2025)
Lyuboira Stefanova, The Palamite Ideas for the Divine Light of the Image in the 14th Century Churches of Thessaloniki. The Palamite Ideas for the Divine Light of the Image in the 14th Century Churches of Thessaloniki. The historical development of the Byzantine Empire in the last period of its heyday (XIII–XIV c.) is marked by political crises, but also by the rise of the theological thought, and the ideas of Hesychasm. The ideas on the transcendental nature of God and the emanation of His energies in the world are at the heart of St. Gregory Palamas’s teaching as he was a defender of the Hesychastic mysticism. The image of God, as the main object of contemplation, provokes the active and creative thought of both the Hesychastic thinkers and the hagiographers of Constantinople and Thessaloniki. Following the iconographic traditions established over the centuries, these ideas on the image and likeness of God are expressed within the philosophy of the uncreated Divine Light. Keywords: Image, Hesychasm, Uncreated Divine Energies, Thessaloniki Churches